The Life of the Afterlife in the Big Sky State : A History of Montana's Cemeteries - Baumler, Ellen (Book collections on Project MUSE., 2021)
"Life of the Afterlife is a ground-breaking history of death in Montana. It offers a unique, reflective, and sensitive perspective on the evolution of customs and burial grounds"--